Pneumonia e vulnerabilidade social : um olhar para família - Souza, Renata Olzon Dionysio de (Universidade Federal de São Carlos, 2016)
Introduction and purpose: Disease of important medical and social impact, pneumonia reaches, especially, the age of children under five years. The family, responsible for child care should be understood in this context. Thus this research aimed to "understand the family as a unit of care in the child's illness situation pneumonia." Methodology: Descriptive documentary research led families of children hospitalized for pneumonia, under 5 years of age from areas of greater social vulnerability, in which the Calgary Family Assessment Model (CFAM) was used for data collection and analysis of results Results: 245 admissions were analyzed, which pointed to 22 families who contemplated the purpose of the study, of which 14 effectively participated in the interview. The application of CFAM granted us to observed families in the life cycle of development of young children, receiving the support of the extended family, using the various health facilities, unordered form and not referenced, with difficult access. The daily activities allowed to observe the care provided to children from the moment of prenatal, through breastfeeding and the mothercraft, in care for the prevention and disease situation. The female figure was more present in the mother's form and support of grandparents, and beliefs permeated the attitudes related to the disease in an attempt to control. Conclusion: This research allowed us to understand how health promotion occurs in the family unit, considering its support and the relationship with the health networks. Regarding the institutions, it was found not to effectiveness in carrying out its role. The model allowed a comprehensive look and systematized the family, demonstrating the need to understand the singularity of each, a movement, essential for nursing, making it possible to build jointly solutions, timely and assertive.
Keywords: Enfermagem pediátrica; Doença respiratória; Hospitalização; Humanização da assistência; Vulnerabilidade social; Família; Relações familiares; Pediatric nursing; Respiratory disease; Social vulnerability; Family; Family relationships; Hospitalization; Humanization of assistance; CIENCIAS DA SAUDE::ENFERMAGEM